Development of innovative polymer-based matricial nanostructures for ritonavir oral administration - Giaretta, Moisele (2019)
Ritonavir is used in the treatment of pediatric human immunodeficiency virus infection. The aim of this study was to develop and evaluate innovative polymer-based matricial nanostructures containing ritonavir for a sustained delivery. Two formulations were prepared by interfacial deposition of preformed polymers using Eudragit® RS100 in combination with Polycaprolactone triol 300 (NPR-300) or Polycaprolactone triol 900 (NPR-900). Ritonavir (1 mgmL-1) was incorporated in the formulations. NPR-300 showed a mean size of 559 nm, SPAN of 1.66, zeta potential of 5.9 mV, pH of 4.23, drug content of 73%, and stability under storage for 15 days. NPR-900 showed a mean size of 120 nm, SPAN of 0.83, zeta potential of 7.0 mV, pH of 4.2, drug content of 81%, and stability under storage for 60 days. The ritonavir content was 100% incorporated in both formulations. TEM images demonstrated spherical matricial structures. The ritonavir release in the simulated gastric medium was controlled by incorporation into the nanoparticles, especially into NPR-900. The formulations showed mucoadhesive properties, and the taste evaluation by an in vivo sensory panel indicated that particle size might influence taste perception since the formulation with the larger size of the nanoparticles (NPR-300) worsened the taste of the suspension. The NPR-900 was the most promising nanoparticle formulation for oral delivery of ritonavir.